Analisis Pengendalian Kualitas Produk Intimates Bra Fused untuk Meminimalkan Defect dengan Menggunakan Metode Six Sigma - Tri Astuti Alawiyah (Manufaktur: Publikasi Sub Rumpun Ilmu Keteknikan Industri, 2024)
PT. Diamondfit Garment Indonesia is a company operating in the apparel industry, especially intimates and swimware. One of the products is the Intimates fused bra. In the production process, many defects are still found. This research aims to propose quality improvements using the six sigma method starting from the define, measure, analyze, improve and control stages. At the define stage, the production process is identified using the SIPOC diagram and identification of the type of defect. At the Measure stage, the calculation stage is carried out: fusing delamination DPMO value 366405.6 with a sigma value 1.84, Wavy At Neckline & Armhole DPMO value 65274.15 with a sigma value 3.01, Molding Yellowish DPMO value 350739.8 with a sigma value 1, 88, Dirty Glue has a DPMO value of 26109.66 with a sigma value of 3.44, and Heat Seal Not Sticking has a DPMO value of 191470.8 with a sigma value of 2.37. As a result of the analysis, it was found that factors causing defects occurred using FMEA tools and fishbone diagrams, namely machine, manpower, material and method factors. In the improvement stage, improvements are made to the factors causing defects and in the control stage, supervision is carried out over the proposed improvements that have been made by creating SOPs.